CREATIVE PROCESS IN FICTION WRITING OF THREE INDONESIAN WRITERS - Iin Nuraeni; Fahrus Zaman Fadhly (University of Kuningan, 2016)
This research investigates the creative process in fiction writing employed by three writers of different writing genres: short story, novel, and poem. This study applied a qualitative method that involved one male and two female writers in Kuningan and Majalengka. The data collected from document analysis, observation, and interview were analyzed through descriptive qualitative method. The results of the analysis revealed that there were five creative processes of writing fiction used by the writers in writing fiction, namely preparation, incubation, insight, evaluation, and elaboration. Besides, it also revealed that novel writer is more creative than short story and poem writers since he uses all steps of creative process. In addition, the researcher found that there were some ways of exploring imagination in writing fiction, including drawing and deepen characters in the film or theater, making mind mapping to write, developing a shorter text, and expecting that the writing will be read by younger generation.Keywords: creative process, writing fiction, fiction writers, imagination process